PEMBUATAN PERMAINAN JEMBATAN PELANGI DAN JUNGKAT JUNGKIT UNTUK MENGEMBANGKAN KEMAMPUAN BERMAIN ANAK DI PAUD MELATI SKB MERAUKE - Klemens Alrin Rahangmetan (Musamus Devotion Journal, 2022)
PAUD is a coaching effort aimed at children from birth to the age of 6 years which is carried out through educational stimuli to help physical and spiritual growth and development so that children have readiness to enter further education. In order to improve the quality and quality of early childhood services, it is necessary to have learning facilities that are in accordance with standards to improve the quality of their services. Playing is one of the means to sharpen a child's brain or psychomotor. Where children can play and learn about their surroundings at the same time. Education has a strategic value in order to form a personality that is knowledgeable, virtuous and has noble character in order to achieve a qualified, advanced and civilized life. In a broad sense, education is a process of developing, fostering and directing individual potential so that they are able to carry out the mandate of leadership. In a broad sense, education aims to foster individual character so that they are able to train skills and skills and practice them in the future. So that to support the formation of a good child's character, of course, it must be supported by good and proper play equipment, the play equipment contained in the Melati SKB Merauke Early Childhood Education certainly does not meet appropriate standards to be used as a means of playing for students who attend school there, so there is a need for improvements.